2021
DOI: 10.3390/genes12040603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Variants in 65 Obesity Related Genes in a Cohort of Portuguese Obese Individuals

Abstract: Obesity is a major public health problem, which has a strong genetic component that interplays with environmental factors. Several genes are known to be implicated in the regulation of body weight. The identification of alleles that can be associated with obesity is a key element to control this pandemic. On the basis of a Portuguese population, 65 obesity-related genes are sequenced using Next-Generation Sequencing (NGS) in 72 individuals with obesity, in order to identify variants associated with monogenic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Next we curated and investigated the gene expression patterns and cell specificity of 94 genes associated with genetic epilepsy (compiled and curated from [59, 60]), 227 Autism Spectrum Disorder (ASD) genes (SFARI Category 1 and SPARK genes[61, 62, 86, 87]), 32 schizophrenia genes [63, 88], 16 dystonia genes [64, 65], 84 genes associated with Alzheimer’s Disease [66], 55 Parkinson’s disease genes from the Gene4PD database [67], 57 Obesity genes [89], and 87 Coronary Artery Disease (CAD) genes [90, 91] (Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…Next we curated and investigated the gene expression patterns and cell specificity of 94 genes associated with genetic epilepsy (compiled and curated from [59, 60]), 227 Autism Spectrum Disorder (ASD) genes (SFARI Category 1 and SPARK genes[61, 62, 86, 87]), 32 schizophrenia genes [63, 88], 16 dystonia genes [64, 65], 84 genes associated with Alzheimer’s Disease [66], 55 Parkinson’s disease genes from the Gene4PD database [67], 57 Obesity genes [89], and 87 Coronary Artery Disease (CAD) genes [90, 91] (Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we identified heterozygous missense variants in SORCS1 in two subjects. Another study investigating genetic variants in 72 individuals with obesity also found two rare missense SORCS1 variants of unknown significance (Ginete et al, 2021). SORCS1 is highly expressed in the central nervous system and encodes a vacuolar protein sorting 10 domaincontaining receptor that binds neuropeptides.…”
Section: Discussionmentioning
confidence: 99%
“…The obesity related genes (ORGs) were collected from the studies of Catarina et al [24] and Ricardo et al [25]. We used the "ConsensuClusterPlus" R package (maxK = 4, reps = 1000, pItem = 0.8, distance="euclidean", clusterAlg="km") to perform consensus clustering and repeat 1000 times.…”
Section: Unsupervised Clusteringmentioning
confidence: 99%